The Research Competence, Critical Thinking Skills and Digital Literacy of Indonesian EFL Students - Indah, Rohmani Nur; Toyyibah; Budhiningrum, Ary Setya; Afifi, Nur (Journal of language teaching and research, 2022)
This project aims to investigate the relationship between English as Foreign Language (EFL) students’ research skills, critical thinking skills, and engagement with technology or their digital literacy. EFL students' research competence is expected to support their academic performance on writing papers and assignments. It also demands the development of their critical thinking skills. Their engagement in technology involves the use of social media, online networks, and the use of several applications. This study takes the sample of EFL students from two institutions, namely UIN Malang and IAIN Kediri, Indonesia, to see whether there is a similar performance in both Islamic higher education institutions in terms of students’ online research competence, critical thinking skills, and similar trend on the engagement with technology. The data collection method covers questionnaire and quiz. This result demonstrates a significant correlation between research competence and digital literacy. Concerning the insignificant relation between digital literacy and critical thinking, it proves that the digital literacy does not always automatically support the enhancement of critical thinking skills. Understanding the relationship between online research competence, critical thinking, and digital literacy is a crucial step in developing Indonesian EFL teaching syllabi and material supporting students' academic success in higher education context.